Case Report: Reversal of Long-Standing Refractory Diffuse Non-Scarring Alopecia Due to Systemic Lupus Erythematosus Following Treatment With Tofacitinib - Chen, Yu-Lan; Liu, Li-Xiong; Huang, Qin; Li, Xue-Ying; Hong, Xiao-Ping; Liu, Dong-Zhou (Frontiers in Immunology, 2021)
The Janus kinases (JAKs) are intracellular tyrosine kinases involved in a broad variety of inﬂammatory cascades participating in the pathogenesis of systemic lupus erythematosus (SLE). Diffuse non-scarring alopecia is one of the most frequent cutaneous manifestations in SLE, resulting in devastating psychosocial consequences. Although recent studies have shown promising outcomes of the JAK inhibitors in SLE treatment, the efficacy of tofacitinib in diffuse non-scarring alopecia due to SLE has never been reported. Here we present a 29-year-old SLE patient with a 10-year history of refractory severe diffuse non-scarring alopecia who experienced dramatic hair regrowth with tofacitinib. Furthermore, we have made a systematic review regarding the potential effectiveness of tofacitinib in systemic and cutaneous lupus erythematosus. To the best of our knowledge, this is the first case study depicting an SLE patient with refractory alopecia who experienced impressive hair regrowth with the JAK1/3 inhibitor tofacitinib therapy, which contributes to expanding the field of possible uses of tofacitinib in SLE patients with difficult-to-treat cutaneous involvement, including severe alopecia.